Literature Review Local and Traditional Knowledge In the Hay River Watershed ... : Tracking Change: Local and Traditional Knowledge in Watershed Governance ... - Wray, Kristine (University of Alberta Library, 2017)
The Hay River Basin has played a vital role in the social, economic, and cultural well-being of many Aboriginal peoples. Given their reliance on and stewardship of its resources, many Aboriginal peoples have developed valuable knowledge about the state of the basin that can contribute to our understanding of historic and contemporary issues of planning, management, and monitoring. The Hay River Basin is a part of the Mackenzie River system, which drains into the Arctic Ocean, drawing water from British Columbia, Alberta, Saskatchewan, and the Northwest Territories. “Kátło’dehé is the South Slavey Dene name for the Hay River, or an earlier spelling Xatlo Dehe” or from the K’átł’odeeche First Nation report, K’átł’odee ‘willow grass river,’ referring to the origins of the river in Hay Lakes, northern Alberta, which is a prairie-like area. In Chipewyan, the Hay River is Hátł’oresche. In Cree, it is Maskosï-Sïpiy” (AANDC 2014). The Hay River is named for the abundant hay fields, which were nourished by the floods ...